Phenotypic variation for BOAS within four brachycephalic dog breeds : can good welfare be obtained? - Bertilsson, Ida (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2019)
Brachycephalic obstructive airway syndrome (BOAS) is an upper airway obstruction that was considered the most severe disorder identified according to the Generic Illness Severity Index for Dogs. The aim of this master thesis was to investigate the phenotypic variance correlated to BOAS in the Swedish population of four brachycephalic breeds; English Bulldog, French Bulldog, Pug and Boston Terrier and discuss their welfare implications. The project consisted of two parts; one inventory and one survey. The inventory consists of conformational description of the four brachycephalic breeds and the survey was to investigate the BOAS related problems in the same breeds and their owner’s perspective of health and welfare. The conformational risk factors correlated to BOAS found in this study were snout length and craniofacial ratio for French Bulldogs, snout length, chest girth, neck length, sternum length and craniofacial ratio for English Bulldogs and none for either Pugs or Boston Terriers. According to the survey noisy breathing and heat intolerance were the most common BOAS-related problems for all the four breeds in this study. The conclusion of the study was that there was enough phenotypic variance to improve the BOAS problem for both French Bulldogs and English Bulldogs. For Boston Terriers the BOAS problem was not severe enough in this study to get a result and for the Pugs the phenotypic variance is too small. For the welfare aspect this study showed that BOAS is a welfare problem and that there was a normalization for some of the problems connected to BOAS for English Bulldogs, French Bulldogs and Pugs.